Simultaneous Quantification of Kirenol, Daurutoside, and Darutigenol in Siegesbeckia orientalis L. by HLPC-DPA Method - Anh, Tran Thi Van; Tuan, Pham Quoc; Khanh, Nguyen Van; Hung, Dao Viet; Hai, Nguyen Thanh; Tuan, Nguyen Quoc; Diep, Nguyen Thi Minh; Thinh, Ngo Thi Xuan; Hoa, Ha Thanh (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 38 No 2, 2022)
Kirenol ( 1 ), darutoside ( 2 ), and darutigenol ( 3 ), which are major active diterpenoids isolated from Herba Siegesbeckiae, are reported for analgesic activity and inflammatory effects. Currently, in Vietnamese Pharmacopoeia V, there is no requirement for the contents of active ingredients in this medicinal plant. In this study, a high-performance liquid chromatography (HPLC) method, which was developed with good repeatability and recovery, was used for simultaneous quantification of 1 , 2 , and 3 in Herba Siegesbeckiae . This method was successfully applied to quantify 1-3 in samples of Herba Siegesbeckiae collected from different locations. The results showed that the content of compound 1 accounted for 0 – 5.77 mg/g, compound 2 ranged from 0.82 to 5.48 mg/g, and compound 3 ranged from 0.37 to 3.18 mg/g. These results are considered a reference for upgrading the specification and quality control of Herba Siegesbeckiae . Keywords: Herba Siegesbeckiae ; kirenol; darutoside; darutigenol; HPLC.